2011
DOI: 10.5014/ajot.2010.ajot00000414
|View full text |Cite
|
Sign up to set email alerts
|

Objectivity and Stability of the Preschool Imitation and Praxis Scale

Abstract: OBJECTIVE.We examined rater and test-retest reliability of the Preschool Imitation and Praxis Scale (PIPS).METHOD. We administered the PIPS to 119 typically developing children ages 1.5-4.9 yr. RESULTS. The PIPS demonstrated acceptable intra-and interrater reliability on item level (k w 5 0.45-1) and scale level (intraclass correlation coefficient ICC 5 0.996; 95% CI: 0.968-0.999 and ICC 5 0.995; 95% CI: 0.990-0.997, respectively). The smallest detectable difference of the PIPS was 5.6%, indicating that the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Results of intra-and interrater reliability of the nine procedural imitation tasks of the PIPS indicated that they can be scored reliably by a trained investigator without video recording. The within-and between-raters weighted kappa values of the sao-P tasks are between .91 and 1.00; of the aso-P tasks between .75 and 1.00, and of the sq-P tasks between .57 and .85 ( Vanvuchelen, et al, 2011d).…”
Section: Measure: Preschool Imitation and Praxis Scale (Pips)mentioning
confidence: 99%
See 2 more Smart Citations
“…Results of intra-and interrater reliability of the nine procedural imitation tasks of the PIPS indicated that they can be scored reliably by a trained investigator without video recording. The within-and between-raters weighted kappa values of the sao-P tasks are between .91 and 1.00; of the aso-P tasks between .75 and 1.00, and of the sq-P tasks between .57 and .85 ( Vanvuchelen, et al, 2011d).…”
Section: Measure: Preschool Imitation and Praxis Scale (Pips)mentioning
confidence: 99%
“…Although these measures rely on a theoretical framework and have consistency in their scores, they pay very limited attention to procedural imitation (Bergès & Lézine, 1963;Užgiris & Hunt, 1987;Ayres, 1989;Korkman, Kirk, & Kemp, 1998). To address this issue, the authors developed the Preschool Imitation and Praxis Scale (PIPS), which was designed to assess the accuracy of bodily and procedural imitation performances in young children (Vanvuchelen, 2009;Vanvuchelen, Roeyers, & De Weerdt, 2011a, 2011dVanvuchelen & Vochten, 2011). The theoretical framework and deductive test construction approach of the Preschool Imitation and Praxis Scale (PIPS) have been described in detail elsewhere (Vanvuchelen, et al, 2011a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, researchers have been hesitant to embrace the full potential of video research. Indeed, the majority of research collects video data to study clinical situations, such as intervention efficacy (Bagatell, Mirigliani, Patterson, Reyes, & Test, 2010), clinical reasoning (Unsworth, 2005), intervention protocol fidelity (Graham, Rodger, & Ziviani, 2013; Parham et al, 2011), intra- and interrater assessment reliability (Spirtos, O’Mahony, & Malone, 2011; Vanvuchelen, Roeyers, & De Weerdt, 2011), and student decision making (Tomlin, 2005).…”
mentioning
confidence: 99%